Study of Correlation of Age and Parity of Mothers with Pre-Eclampsia in Pregnant Women in the Working Area of Mangasa Health Center in Makassar City - Alfi Syahar Yakub; Iwan Sain; Sukma Saeni (Media Kesehatan Politeknik Kesehatan Makassar, 2019)
Preeclampsia is the onset of hypertension with proteinuria due to pregnancy, after 20 weeks' gestation or immediately after delivery. These symptoms can occur before 20 weeks if trophoblastic disease occurs. This study aims to determine the relationship between age and maternal parity with the incidence of pre-eclampsia in pregnant women in the work area of the Puskesmas Mangasa, Makassar City. The research design used in this study was descriptive analytic research with a cross sectional study design. Conducted from July to October 2018, with a sample of 70 respondents. In this study showed that there was no relationship between the age of pregnant women and the incidence of preeclampsia with a value of p (1.00)> 0.05 and there was no relationship between parity and the incidence of preeclampsia with a value of p (1.00)> 0.05. It is recommended for health workers to be intensive in detecting the presence of preeclampsia in pregnant women and counseling about the importance of routine antenatal care to as early as possible be aware of the risk of the occurrence of preeclampsia-eclampsia in pregnancy and for further researchers, further research is needed to find factors related to the incidence of preeclampsia so that the results are in accordance with the theory, such as parity, hypertension history and Antenatal Care examination.